PARTICLE SWARM OPTIMIZATION AND GRIDSEARCH OPTIMIZATION ON SUPPORT VECTOR MACHINE ALGORITHM ON SENTIMENT ANALYSIS OF DONALD TRUMP'S ASSASSINATION ATTEMPT - Putra, Rinaldi Febryatna Duriat; Sudewo, Andika Hasbigumdi; Wibowo, Arief (Informatika, Universitas Jenderal Soedirman, 2024)
Donald Trump is the 45th president of the United States, serving from 2017 to 2021. Within the 2024 race, Donald Trump is once more running for president of the United States from the Republican Party. Whereas campaigning in Butler, Pennsylvania, United States, a shooting occurrence happened that was distinguished as an endeavored death of Donald Trump. The occurrence gave rise to different master and con opinions among the open. This consider points to decide the propensity of open conclusion towards the endeavored death of Donald Trump and to classify estimations with respect to the occurrence. This think about compares the Molecule Swarm Optimization (PSO) and GridSearch optimization approaches on the Back Vector Machine (SVM) calculation to get the greatest level of precision from optimizing the calculation. In this think about, the dataset utilized was tweet information from July 15, 2024, totaling 1,586, which had been labeled with positive, neutral and negative estimations. The comes about of the tests carried out with comparison proportions of 90:10, 80:20, 70:30, and 60:40 appear that the optimization strategy through PSO can increment the exactness of the SVM calculation by 2.39% when compared to the GridSearch strategy.